2002
DOI: 10.1177/0306624x02464004
|View full text |Cite
|
Sign up to set email alerts
|

Extent and Characteristics of Woman Batterers among Federal Inmates

Abstract: Efforts to identify men who batter women in clinical settings have increased in recent years, but batterer research in United States federal prisons is lacking; low security federal prisons are logical places to consider batterer screening and treatment given the number of men, the domestic violence "risk markers" associated with these men and the likelihood they will be released and return to female partners. This study examined intake assessment data for 115 low security federal inmates. The inmates evidence… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
0
1

Year Published

2006
2006
2019
2019

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(15 citation statements)
references
References 19 publications
1
13
0
1
Order By: Relevance
“…Westen et al [38] found that paranoid, antisocial, borderline, histrionic, and narcissistic traits all correlated with aggression scores in adolescent outpatients. White et al [32] found comparable findings in a prison population.…”
Section: Evidence For Increased Risk Of Violence In Borderline Personmentioning
confidence: 68%
See 2 more Smart Citations
“…Westen et al [38] found that paranoid, antisocial, borderline, histrionic, and narcissistic traits all correlated with aggression scores in adolescent outpatients. White et al [32] found comparable findings in a prison population.…”
Section: Evidence For Increased Risk Of Violence In Borderline Personmentioning
confidence: 68%
“…In general, most of the cross-sectional studies found that some measure of BPD correlated positively with measures of aggression, whether that measure was BPD scores on personality measures [29][30][31][32], number of DSM-IV BPD criteria [33][34][35], or meeting criteria or cutoff score for BPD [32,36,37].…”
Section: Evidence For Increased Risk Of Violence In Borderline Personmentioning
confidence: 99%
See 1 more Smart Citation
“…Esta deve ocorrer, de preferência, num ambiente estruturado, sob a alçada de qualquer medida de controlo penal, para que o agressor sinta que, se não aderir ao projecto de mudança que lhe é proposto, as consequências de tal atitude serão tidas em conta na avaliação dessa medida (e.g., Gordon & Moriarty, 2003;Stroshine & Robinson, 2003). A investigação disponível sugere ainda que, tal como no caso de outros agressores, os ofensores conjugais revelam comportamentos anti-sociais noutras áreas, nomeadamente abuso de substâncias e perturbações emocionais, pelo que se justifica uma preocupação de rastreio de comportamentos familiares abusivos nas populações de toxicodependentes para que o tratamento destes não contemple apenas a vertente da desintoxicação (e.g., Logan, Walker & Leukfeld, 2001;White, Gondolf, Robertson, Goodwin & Caraveo, 2002).…”
Section: Conclusãounclassified
“…The benefit of participating in a program while in the institution, may lead to higher rates of completion and enhanced motivation to change (Polasheck et al, 2005;Bennett et al 2007) as was experienced by this project. Numerous researchers have recommended the inclusion of family violence issues, specifically domestic violence interventions as part of the rehabilitative process in correctional settings (White et al, 2002;Williams, 2006;Dutton, 1992). Accreditation of the programs is equally important, to Batterer's Intervention Program 467 ensure that the same standards are being implemented in the institution, as is required in the private counseling programs.…”
Section: Future Potential and Research Implicationsmentioning
confidence: 99%